"It Has Changed My Life": An Exploration of Caregiver Experiences in Serious Illness. (February 2018) - Anderson, Eric W.; White, Katie M.
Background: Informal, unpaid caregivers shoulder much of the care burden for individuals with serious illness. As part of a project to create an innovative model of supportive care for serious illness, a series of user interviews were conducted, forming the basis for this article. Objective: To understand both individual and interpersonal aspects of caregiving for serious illness. Methods: Twelve semistructured group interviews were conducted with patients, families, and professionals as part of a larger study of late-life serious illness. Transcript data were analyzed with descriptive coding, and then coded material was analyzed to elicit major themes and subthemes. Results: A total of 73 individuals participated in group interview sessions. Using descriptive coding, quotes were assigned to first-order codes of rewards, challenges, and a category of learnings and adaptations. Subthemes of reward included gratitude, a sense of accomplishment or mastery, and closeness in personal relationships. The most oft-cited challenges included emotional and physical stresses of caregiving and feeling unprepared or unsupported in caregiving. Reflecting on their experiences, caregivers cited new ways in which they had learned to be creative, to show assertiveness and advocacy, and to create personal balance in a demanding situation. Conclusions: The experience of caregiving is a life-altering journey as individuals rise to challenges and reflect on the rewards. Caregivers described intensive caregiving, often without acknowledgment or understanding of their role from the health-care system. This invisibility created its own iatrogenic caregiving challenge. The identified themes suggest avenues of meaningful caregiver support that bear further exploration.